T. S. Eliot's ‘Ash‐Wednesday’ and Four Quartets: Poetic Confession as Psychotherapy - Brown, Dennis (Literature and theology, 2003)
The article considers T.S. Eliot's ‘Ash‐Wednesday’ and Four Quartets as confessional poetry in a double sense—as interpersonal communication before God, and to the reader. It is thus akin to the relationship between therapist and client in a counselling situation. ‘Ash‐Wednesday’ constitutes a Lenten preparation in which understanding is sought by means of an articulation of failure, loss and repentance. Four Quartets uses a similar confessional technique, evoking ‘peak’ moments (both primal scene and the site of mourning) out of which religious philosophising emerges as proposed ‘interpretation’. It is suggested that the poems resemble a confidential ‘talking cure’.